Using the General Level Framework to guide training and development needs of pharmacists working in paediatrics. (September 2015) - Stacey, Sonya R.; Coombes, Ian; Cardiff, Lynda; Wainwright, Claire; Whitfield, Karen M.
Abstract Background The 'General Level Framework' (GLF) has been used for many years as a tool for competency evaluation and feedback using direct observation of clinical practice; however, its use in the paediatric environment has not been investigated. Aim To identify the strengths and training and development needs for paediatric pharmacists using the GLF. Methods Retrospective analysis of evaluations of paediatric pharmacists in Queensland hospitals using the GLF. Pharmacists from specialist paediatric hospitals were compared with those from general hospitals. Results A total of 50 GLF evaluations undertaken between 2006 and 2011 were identified from ten hospitals. Competencies related to ethical practice, confidentiality and ensuring prescriptions are legal with appropriate doses, were performed well. Assessment of patient's understanding of illness and treatment, and adherence, or documentation of pharmacist interventions and medication action plans were not performed consistently well. Knowledge of pathophysiology, assessment of patient's experience and management of medicines were demonstrated more consistently in the paediatric hospitals than in general hospitals. Conclusion A generic tool such as the GLF can be used in specialist areas such as paediatrics to identify priority training areas for pharmacists working in clinical practice.